Robotics and AI for social justice: new perspectives between assistance, education and ethical reflection - Seidita, Valeria; Bongiorno, Rosario; Franco, Daniele; Giambanco, Alessandro; Randazzo, Gianni; Sciacchitano, Antonio Pio; Chella, Antonio (Filosofia Morale/Moral Philosophy, 2025)
Artificial intelligence and robotics are changing the way we approach societal challenges, offering new opportunities to improve inclusion, access to care and ethical reflection. Although concepts such as introspection, consciousness and ethical reflection are the subject of wide philosophical debate, the aim of this paper is not to discuss them theoretically, but to explore how some of their dimensions can be captured in simplified computational models, with practical applications in the context of AI and robotics. This article explores the potential of these technologies to promote social justice. Two main application areas are analyzed: assisting vulnerable individuals, such as the elderly and people with disabilities, and the ability of robots to promote awareness and change in educational contexts. Experiments in the healthcare and school sectors will be used to demonstrate how technology can be used to optimize services and to stimulate critical reflection on the dynamics of exclusion and acceptance. However, the potential of AI and robotics comes with significant ethical challenges, such as the risk of bias and new forms of surveillance. The work emphasizes the importance of a responsible approach to technological development so that innovation can be guided by principles of justice and inclusion rather than purely economic or efficiency logics.